Objects of journalism and the news. (January 2015) - Anderson, CW; De Maeyer, Juliette
This article provides an overview of what an "object-oriented" approach to journalism studies might look like, based on a survey of articles collected for this special issue on journalism and materiality. We argue that focusing on the objects of journalism, rather than limiting or trivial, can provide scholars with insights into the social, material, and cultural context that suffuses our technologically obsessed world. The article pushes back against a dominant perspective in the Actor-Network Theory literature that sees the major value of that theory in studying technological innovation, calling instead for a theoretical approach open to questions of historical change, power, and symbolic practices.